2005
DOI: 10.1186/1477-7525-3-54
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a psychosocial screening instrument for cancer

Abstract: BackgroundWe are reporting on the development of a psychosocial screening tool for cancer patients. The tool was to be brief, at a relatively low reading level, capture psychological variables relevant to distress and health-related quality-of-life in cancer patients, possess good reliability and validity, and be free of copyright protection.MethodItem derivation is described, data on reliability and validity as well as norms are reported for three samples of cancer patients (n = 1057; n = 570, n = 101).Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The Social Network and Support Assessment (SNSA) is a 17 item measure assessing multiple dimensions of perceived support, used previously in studies of cancer survivors [32, 33] and derived from an epidemiological study of social networks among older adults [34]. Respondents are asked to characterize the level of support they receive from various sources, including their relationship partners.…”
Section: Methodsmentioning
confidence: 99%
“…The Social Network and Support Assessment (SNSA) is a 17 item measure assessing multiple dimensions of perceived support, used previously in studies of cancer survivors [32, 33] and derived from an epidemiological study of social networks among older adults [34]. Respondents are asked to characterize the level of support they receive from various sources, including their relationship partners.…”
Section: Methodsmentioning
confidence: 99%
“…The HRQOL-4 developed by CDC has undergone extensive reliability and validity testing and has demonstrated adequate psychometric properties. 20-24 …”
Section: Methodsmentioning
confidence: 99%
“…Previous validation research found that both cancer outpatients ( d  = 0.26, p  < 0.001) as well as cancer inpatients ( d  = 0.70, p  < 0.001) reported significantly higher levels of depression compared to a community sample [25]. Age was negatively associated with depression in patients with cancer ( ρ  = −0.157, p  < 0.001) as well as in a healthy community sample ( ρ  = −0.190, p  < 0.001) (unpublished data derived from the validation samples).…”
Section: Methodsmentioning
confidence: 99%